Organ transplants : the anencephalic fetus may be a potential donor ? - Arribalzaga, Eduardo (2001)
In the beginning of a new millennium , the countless everyday technological advances result in new ethical questions , some difficult approach and unknown current solution. As there is a permanent reality and questioning the ethical principles , the dilemma comes in thinking that ethics moves on a different plane of self- care activities of daily when really the development of medicine (with its technical progress ) and ethical standards run parallel in the same direction . These seemingly abstract but permanently effective , ethical standards can solve different problems, but many of them are absolutely new for novelty (1). Takes account of situations or dilemmas of increasing complexity, which must be recognized by a thorough search, not to underestimate the desire of patients overestimate the magnitude of their decisions or excess revalue the opinion of specialists or experts.